Challenges to Treating Older Glioblastoma Patients: the Influence of Clinical and Tumour Characteristics on Survival Outcomes. Issue 11 (November 2017) - Lorimer, C.F.; Hanna, C.; Saran, F.; Chalmers, A.; Brock, J.
Abstract: Aims: There is now evidence to support giving single-agent chemotherapy, radiotherapy or hypofractionated concurrent chemoradiotherapy to older patients with glioblastoma (GBM). However, the clinical basis on which treatment decisions are made is under-researched and not standardised. This retrospective, multicentre study assessed whether pre-morbid characteristics or tumour imaging features could predict for overall survival in a cohort of older patients with GBM. Materials and methods: Patients aged > 70 years, diagnosed with GBM at three neuro-oncology centres from 2010 to 2015 were retrospectively analysed. Demographic, clinical, radiological and treatment details were included in a multivariate model to examine for predictors of overall survival. Results: In total, 339 patients were included with a median overall survival of 3.8 months. One and 2 year overall survival rates were 13% and 4%, respectively. The median age at diagnosis was 75 years. Pre-treatment characteristics predicting for overall survival included Eastern Cooperative Oncology Group performance status over 0 (performance status 1, hazard ratio 1.66, P  = 0.042; performance status 2, hazard ratio 1.78, P  = 0.031; performance status 3, hazard ratio 2.20, P  = 0.008; performance status 4, hazard ratio 2.40, P  = 0.021), radiological evidence of mass effect (hazard ratio 1.31, P  = 0.049), multifocal tumours (hazard ratio 3.419, P  = 0.013), presenting with seizures (hazard ratio 0.63, P  = 0.008) and tumours confined to the cerebral hemisphere (hazard ratio 0.59, P  = 0.048). Subtotal resection decreased risk of death by 37% ( P  = 0.019) and total tumour resection by 44% ( P  = 0.019). Palliative radiotherapy decreased risk of death by 41% ( P  = 0.005), temozolomide alone by 60% ( P  = 0.004) and radical chemoradiotherapy by 81% ( P  < 0.001). Conclusion: Clinical presentation, performance status and imaging characteristics are independent prognostic indicators of overall survival in older GBM patients, irrespective of age or treatment received. Highlights: Median life expectancy is only 3-5 months for older patients with glioblastoma (GBM). There is an urgent need to improve outcomes, reduce toxicity and maintain quality of life. Pre-morbid and imaging characteristics are independent prognostic indicators of survival. This provides a basis for prospective studies to holistically assess older GBM patients for treatment.